PERGESERAN PELAKSANAAN RAMPANAN KAPA’ PADA MASYARAKAT TORAJA DI TONGKONAN PALAWA’ KELURAHAN PALAWA’, KECAMATAN SESEAN KABUPATEN TORAJA UTARA - Delfia Tia Palintin; Firdaus w Suhaeb; Nurlela . , (Universitas Negeri Makassar, 2022)
ABSTRACTThis research aims to find out: (1). How the form of shifting Kapa's Rampage. (2) factors that influence the shift in value in the implementation of the Kapa's Rampan tradition. (3) The perception of Indigenous peoples and millennials about The Kapa' Rampage' is now undergoing a shift. This type of research is qualitative in a descriptive nature, which is research that describes certain situations based on data obtained in detail through observations, interviews, documents and documentation, involving several informants, namely indigenous figures, community leaders, religious figures, indigenous actors, indigenous peoples, and millennials. The results of research that has been done, show that (1) The tradition of marriage of the Toraja people namely Rampanan Kapa' has undergone changes in the community in Palawa Village' in its implementation such as the tradition of food umbawa has not been practiced, as well as the loss of customary marriage law, the function of Tongkonan that began to be ignored, different marriages of cultures or tribes that have occurred, and the use of kapa' looting that is diverse and modern, Of course this makes the loss of value and meaning that is in it as the identity of the Toraja community. (2) The changes that occur are caused by several factors, such as the development of science and technology, the entry of religion, openness to the level of society, having an orientation in the future, and increasing the number of population. (3) Palawa people's perception of this, they can accept the Kapa's Spoils with the changes that occur in it due to the inevitable development of the times and it is impossible to maintain the original tradition, they have their own judgment from the positive and negative side caused.